1998
DOI: 10.1007/pl00005214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term administration of duloxetine on the function of serotonin and noradrenaline terminals in the rat brain

Abstract: Duloxetine, an inhibitor of both 5-hydroxytryptamine (5-HT) and noradrenaline (NA) reuptake processes, has been developed as a potential antidepressant drug. The present study was initiated to investigate the functioning of multiple components of the 5-HT and NA systems following the long-term administration of duloxetine. In rats treated for 21 days with duloxetine (20 mg/kg/day), the recovery times of dorsal hippocampus CA3 pyramidal neurons from microiontophoretic applications of 5-HT and NA were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…As compared to controls, the 140% increase in CA 3 pyramidal neuron firing in response to i.v. administration of the selective 5-HT 1A receptor antagonist WAY 100,635 (Figure 8,Panel B,and Figure 9), is well within the range of that produced with other antidepressant treatments (Béïque et al 2000;Rueter et al 1998;Haddjeri et al 1998), with lithium addition and even to a greater extent with the combination of mirtazapine and paroxetine than either drug alone (Besson et al 2000). It is interesting to note that the latter strategies are endowed with a greater antidepressant efficacy (Rouillon and Gorwood 1998;Debonnel et al 2000).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As compared to controls, the 140% increase in CA 3 pyramidal neuron firing in response to i.v. administration of the selective 5-HT 1A receptor antagonist WAY 100,635 (Figure 8,Panel B,and Figure 9), is well within the range of that produced with other antidepressant treatments (Béïque et al 2000;Rueter et al 1998;Haddjeri et al 1998), with lithium addition and even to a greater extent with the combination of mirtazapine and paroxetine than either drug alone (Besson et al 2000). It is interesting to note that the latter strategies are endowed with a greater antidepressant efficacy (Rouillon and Gorwood 1998;Debonnel et al 2000).…”
Section: Discussionsupporting
confidence: 60%
“…The average number of spikes suppressed from baseline firing activity of hippocampus neurons during microiontophoretic applications of NE and 5-HT provides a reliable index of the sensitivity of postsynaptic ␣ 2 -adrenergic and 5-HT 1A receptors, respectively (Curet and de Montigny 1988a;Rueter et al 1998). These values generated from microiontophoretic applications of NE and 5-HT on the firing activity of CA 3 pyramidal neurons was significant (F 2,122 ϭ 15.4 and F 2,120 ϭ 11.3, respectively; p Ͻ .001 for both monoamines) and currentdependent ( p Ͻ .05 for both monoamines), meaning that increasing ejection currents enhanced the number of spikes suppressed following NE and 5-HT ejections from the micropipette, examples of which are provided in Figure 1.…”
Section: Effects Of Acute Reboxetine Injections On the Response Of Camentioning
confidence: 99%
“…Hipp, hippocampus; CP, caudate putamen; Hyp, hypothalamus; other abbreviations are as indicated in the text noted that the antidepressant effects of SNRIs involve noradrenergic modulation of 5-HT neuronal function via the desensitization of a 2 adrenoceptors on the terminals of 5-HT neurons [52,[107][108][109] rather than the facilitation of noradrenergic neurotransmission. Furthermore, it has been demonstrated that milnacipran reduced immobility time in NA-depleted rats [52], suggesting that milnacipran could exert 5-HT-related antidepressive effects in addition to causing alterations to NA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The cyclic antidepressant drugs, potent inhibitors of noradrenaline and/or serotonin (5-hydroyxytryptamine; 5-HT) reuptake in neurones, represent the most commonly used pharmacological agents for the treatment of depressive illness (see Delgado et al 1992). These drugs are rapidly effective in blocking noradrenaline and/or 5-HT reuptake (Owens et al 1997), which is followed by modulation of neuronal discharges (Svensson and Usdin 1978;Chaput et al 1986;Lacroix et al 1991;Mongeau et al 1994;Rueter et al 1998) and neurotransmitter release (Crews and Smith 1978;Feuerstein et al 1993;Mongeau et al 1993;Blier and Bouchard 1994;Auerbach and Hjorth 1995). The mechanism involved in these adaptive neuronal processes is related to the indirect modulation, by the neurotransmitter acting as the endogenous agonist, of somatodendritic and nerve terminal autoreceptors and/or heteroreceptors in noradrenergic and serotonergic neurones.…”
Section: Introductionmentioning
confidence: 97%